Technologies in smart agriculture: Efficiency and sustainability (Research, Society and Development, 2024)
Population growth requires an increasing demand for food and puts increasing pressure on natural resources. To provide food for the next generations, agricultural activities must become increasingly productive and sustainable. Digital technologies emerge as great allies for sustainable agricultural development, increasing productivity, reducing pollutant emissions and improving the conservation of natural resources. In agriculture, the automation of machines and implements, combined with the use of information technologies for data acquisition and production system management, are the main topics used to form a management system known as Precision Agriculture (AP). These new technologies, some in development and others already operational, have been a recurring topic in the current scientific community. In this work, we seek to understand which emerging technologies have recently been highlighted in agricultural activity and what advances and challenges these technologies face. The research indicated that technologies such as: Internet of Things (IoT), Robotics, Artificial Intelligence and (Big Data) are being widely used with promising results for the agricultural sector. However, there are still important challenges for digital transformation to integrate different scientific, technological, social and economic agricultural classes and regions.